Long-Term Evaluation of Capsulotomy Shape and Posterior Capsule Opacification after Low-Energy Bimanual Femtosecond Laser-Assisted Cataract Surgery. (23rd September 2020) - Verdina, Tommaso; Peppoloni, Chiara; Barbieri, Lucrezia; Carbotti, Maria Rosaria; Battaglia, Bruno; Mastropasqua, Rodolfo; Cavallini, Gian Maria
Abstract : Purpose . To evaluate capsulotomy shape and posterior capsule opacification (PCO) during an 18-month follow-up for bimanual femtosecond laser-assisted cataract surgery (FLACS). Methods . 74 eyes operated by a well-trained surgeon with bimanual FLACS technique using low-energy LDV Z8 (Ziemer Ophthalmic Systems AG, Port, Switzerland) were included in the study. The follow-up period was 18 ± 2 months. Another 91 eyes, which underwent standard bimanual microincision cataract surgery (B-MICS), served as a control group. In all cases, a BunnyLens AF (Hanita Lenses, Israel) intraocular lens was implanted in the bag. A digital image of the capsule with slit-lamp retroillumination was performed in all patients at 18 months of follow-up. Image analysis software (ImageJ) was used to evaluate the shape of the capsulotomy in terms of diameter, area, and circularity. PCO score was evaluated using EPCO 2000 software. Best corrected visual acuity (BCVA) and endothelial cell count (ECC) were evaluated before and after surgery at 1 and 18 ± 2 months. Results . At 18 months, mean capsulotomy diameter was 5.34 ± 0.21 mm while capsulorhexis was 5.87 ± 0.37 mm (p < 0.001 ) and the deviation area from baseline was 1.13 ± 1.76 mm 2 in FLACS and 2.67 ± 1.69 mm 2 in B-MICS (p < 0.001 ). Capsulotomy circularity was 0.94 ± 0.04 while capsulorhexis was 0.83 ± 0.07 (p < 0.001 ). EPCO score was 0.050 ± 0.081 in the FLACS group and 0.122 ± 0.239 in the B-MICS group (p = 0.03 ). The mean BCVA improvement was significant in both groups, without a significant difference at 18 months. We noticed a statistically significant difference in endothelial cell loss at 18 months (FLACS 12.4% and B-MICS 18.1%; p = 0.017 ). Conclusions . Bimanual FLACS is a safe and effective technique, as determined in a long-term follow-up. Capsulotomy shape presented higher stability and circularity in the FLACS group over the 18-month observation period. FLACS resulted in lower PCO scores and endothelial cell loss at 18 months in comparison to B-MICS standard technique.